Comparison of different indices of heart rate variability as indicators of parasympathetic reactivation after maximal exercise: brief report (Revista horizonte, 2014)
Context: Heart rate recovery (HRR) is associated with parasympathetic reactivation. Obtain sensitive indicators of vagal activity is important to control internal training loads. Purpose: To compare different indicators of HRV in the time domain related to vagal activity and determine what could be more appropriate for assessing parasympathetic reactivation after maximal exercise in healthy trained subjects. Methods: Nine male subjects performed an incremental test with an initial velocity of 7 km h- 1 and an inclination of 0%. The speed was increased every minute in 1 km h-1 until exhaustion to obtain the peak treadmill velocity (PTV). Linear analysis of HRV was assessed using root mean square of the difference of successive R-R intervals (rMSSD) and standard deviation of normal R-R intervals (SDNN), and nonlinear analysis of HRV was assessed by standard deviation of instantaneous (SD1) beat-to-beat R-R interval variability. In addition, the HRR was calculated at 30 and 60 s (Î”HRR30s and Î”HRR60s respectively). Results: Significant differences between SDNN and rMSSD (p